Building Resilient Muslim Families: An Analysis of Resilience Based on the Qur'an and Hadith - Ridlwan, Muhamad Khoiri; Fitriana, Evi (Studi Multidisipliner: Jurnal Kajian Keislaman, 2024)
This study aims to explore the concept of family resilience from an Islamic perspective based on the Qur'an and Hadith and evaluate its relevance to modern Muslim family life. Islam emphasizes the importance of values such as taqwa (piety), tawakkal (trust in Allah), ṣabr (patience), gratitude, and raḥmah (compassion) in building a strong and harmonious family. This research employs a qualitative approach with library research methods. Primary sources include the Qur'an, authentic Hadith, and tafsir, complemented by secondary literature such as academic journals and books on Islamic family jurisprudence. Thematic interpretation methods were used to identify key Islamic values relevant to family resilience. The findings reveal that Muslim families applying Islamic principles such as open communication (shura), patience, and gratitude are better equipped to face modern challenges, including economic pressures, family conflicts, and technological influences. Religious education also plays a vital role in shaping resilient generations capable of adapting to changes without losing spiritual identity. In conclusion, family resilience in Islam not only provides spiritual guidance but also practical solutions to contemporary challenges. Integrating Islamic values into modern life practices can create harmonious, stable, and resilient families.